Rāingān sarup phon kānwikhr̨o kh̨̄omūn nisit mai Čhulālongk̨̄onmahāwitthayālai, pī kānsưksā 2537 (K̨̄ong Ph̄ænngān, Fāi Wāngph̄æn læ Phatthanā, Samnakngān ʻAthikānb̨̄odī, Čhulālongk̨̄onmahāwitthayālai, 1994)
Report of survey on new admissions in various departments and schools of Chulalongkorn University, academic year 1994.